Morphometric Parameters of Leukocytes in the Management of Sepsis Running Title: Cell Population Data in Sepsis - Eloísa Urrechaga (Highlights on Medicine and Medical Research Vol. 9, 2021)
Sepsis is a medical emergency that explains the body’s systemic immune response to an infection which can result in organic dysfunction and death at the end of the process. Sepsis is a complex inflammatory syndrome, severe, high prevalent, severe and health care burden disease. Despite the advances in understanding the pathophysiology of this syndrome and therapies, sepsis remains one of the leading causes of morbidity and mortality in critically ill patients. Early diagnosis and rapid intervention are essential to improve outcomes, which inspired the concept "golden hour," during which the correction of shock and organic dysfunction can improve the patients ´outcomes. But the initial presentation of sepsis is often nonspecific and its severity is difficult to assess. Anomalies in temperature, heart and respiratory rates and leukocyte counts are manifestations of systemic inflammatory response syndrome (SIRS). Diagnosis, management, and follow-up of sepsis patients remain difficult, and a number of biomarkers have been suggested for early diagnosis and prognosis of septic patients, including lactic acid, procalcitonin, C-reactive protein, and immature granulocytes. Infection causes a humoral, cellular, and neuroendocrine response in the host, and leukocytes interact with endothelial cells. The new generation of hematological analyzers incorporates technological innovations allowing to expand the information derived from the complete blood count: new leukocyte derived parameters are emerging as potentially useful markers in different clinical situations. Additional criteria for analysis Cell Population Data (CPD), which characterises various leukocyte populations, has recently become available, and preliminary findings indicate that they may be useful in the diagnosis of sepsis. This review emphasises the importance of CPD for early detection of sepsis, as stated by modern cellular counters, and thus the possible improvement in patient outcomes.